Socioeconomic Analysis of the Utilization of Health Facilities for Outpatient Care in West Java Province: Analysis of 2024 SUSENAS Data - Jati Setyo Dwi Susanti Jati Setyo Dwi Susanti; Kurnia Sari; Salma Nusaiba (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
This study aims to analyze the influence of socioeconomic factors on the utilization of health facilities for outpatient care in West Java Province. A quantitative approach with a cross-sectional design was employed using data from the 2024 National Socioeconomic Survey (SUSENAS). The study sample consisted of 9,523 individuals. Data analysis was conducted descriptively, bivariately using the chi-square test, and multivariately using binary logistic regression. The results indicate that age, employment status, economic status, and health insurance ownership have a significant effect on the utilization of outpatient services. Individuals of productive and older age, those who are employed, with higher economic status, and possessing health insurance are more likely to utilize outpatient services. In contrast, education level does not show a significant effect. These findings confirm that socioeconomic factors remain key determinants in the utilization of health services; therefore, health policies should focus on reducing economic and structural barriers to promote equitable access to care.